Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose This report presents long-term outcomes of third-generation anti-CD30 CAR T-cell therapy in relapsed/refractory (r/r) CD30+ lymphoma patients. Patients and methods In this single-arm, multicentre, phase 1/2 trial, patients received lymphodepletion regimen comprising fludarabine and cyclophosphamide, followed by infusion of anti-CD30 CAR-T cells. Primary endpoints included safety and overall response rate (ORR), while secondary endpoints were progression-free survival (PFS) and overall survival (OS). Results Forty-four patients were enrolled, including 33 cases of Hodgkin lymphoma. Of 44 patients, 23 achieved complete response (CR) to CAR-T, and 19 achieved PR, resulting in a CR rate of 52.3% and an ORR of 95.5%. The most frequent toxicities were hematologic AEs of grade 3 or higher (68.2% of neutropenia). Cytokine release syndrome occurred in 18 patients (40.9%), with two cases (4.5%) being ≥ grade 3. In the follow-up period, 24 patients underwent auto-HSCT after CAR-T within a median of 3 months. The best ORR was 95.5%, with 27 patients (61.4%) achieving CR. The best CR rate was higher in patients receiving CAR-T followed by auto-HSCT compared to those receiving CAR-T alone (75% vs. 45%). 3-year OS and PFS rates for all patients were 79.0% (95%CI, 66.1%-91.9%) and 74.2% (95%CI, 60.3% -88.1%). Patients receiving consolidated auto-HSCT following CAR-T exhibited significantly longer OS and PFS compared to those treated with CAR-T alone. Conclusion Third-generation anti-CD30 CAR-T demonstrates high efficacy and a favorable safety profile in r/r CD30+ lymphoma patients. Addition of auto-HSCT following CAR T-cell therapy improves depth of remission and potentially enhances OS and PFS.